Gesondheidsdienste en Verantwoordelikhede Onder die nuwe Wet van 1977 - J. Gilliland (AOSIS, 1978)
Health services and responsibility under the new Health Act Summary A brief historical sequence of events leading to the promulgation of the Health Act of 1977 is described. The philosophy of the new Act is discussed stressing the flexibility of health services by the three levels of Government. The policy of consultative policy-making and coordinated decentralised execution is discussed and an outline given of possible responsibilities.